Exercise training decreases body mass index in subjects aged 50 years and over - Haryono, Ignatio Rika (Universa Medicina, 2010)
Exercise training can improve blood pressure in normotensive, prehypertensive, and hypertensive subjects. One of the mechanisms of blood pressure reduction in hypertensive patients with obesity is through weight loss. This study aimed to examine the effect of exercise training on bodyweight and the relationship between weight loss and reduction of blood pressure. An experimental pre-post test design without controls was used to evaluate the effect of exercise training on weight loss. The study involved 89 elderly aged 50 years or more, consisting of 40 men and 49 women, who were members of Senayan Sport Fitness Club and had been exercising for at least three months. Exercise training was programmed and performed three times a week, consisting of aerobic (walking, jogging, static cycling), and resistance exercise. All exercise was performed for one to two hours with mild to moderate intensity. Blood pressure and body weight were obtained from medical records. Paired t-test showed that systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), pulse pressure (PP), and body mass index (BMI) were significantly lower after training [(systolic, 126.3 ± 2.9 vs 122.3 ± 2.7, p=0.02), (diastolic, 80.2 ± 3.1 vs 77.2 ± 2.4, p=0.00), (MAP, 95.6 ± 4.6 vs 92.2 ± 3.4, p=0.00), (PP, 46.1 ± 4.2 vs 45.1 ± 3.6, p=0.04), (BMI, 24.5 ± 2.9 vs 23.6 ± 2.9, p=0.04)]. Duration of training was the most influential factor affecting rBMI, (Beta = 0.38; p=0.00). Exercise training could lower BMI and the reduction in diastolic blood pressure was higher for the subjects aged 70 years and over.